The Role of Sustainability Accounting in Improving Environmental Performance in Vietnam's Manufacturing Industry - Pham Huy, Hung (Indonesian Journal Publisher, 2024)
This research addresses the question of how sustainability accounting practices influence environmental performance in Vietnam’s manufacturing sector, filling a gap in understanding how these practices are applied in developing economies. The purpose of the study is to explore how sustainability accounting impacts key environmental metrics such as emissions reduction, waste management, and energy efficiency, and to identify the challenges faced by companies in implementing these practices. A qualitative case study methodology was used, involving semi-structured interviews with 15 participants from 5 manufacturing companies across various sectors (e.g., textiles, electronics, food processing). The research found that while sustainability accounting is helping companies improve their environmental performance, challenges such as limited resources, lack of expertise, and insufficient regulatory support hinder broader adoption. The results are significant because they highlight the potential for sustainability accounting to drive environmental improvements, but also emphasize the need for increased investment in technology, capacity building, and stronger regulatory frameworks. These findings provide practical recommendations for Vietnamese manufacturers to enhance their sustainability accounting practices, which is increasingly important as they seek to meet global sustainability standards and improve their competitiveness in international markets.